(untitled) (Global Journal of Science Frontier Research, 2020)
This Research Was Conducted In S/N/N/P/R/S; Hadiya Zone; Analemo Woreda; On Title Of Sheep And Goat Fattening Practice And Marketing System In 2011 E.C. The Objective Of The Study Was Assessing Sheep And Goat Fattening Practice And Marketing System Of In The Study Area. The Kebeles Of The Study Area Were Purposively Selected Based On The Accessibility, Sheep And Goat Fattening Practice, And From These Kebeles Respondents Were Selected By Systematic Random Method. In This Study Both Primary And Secondary Data; Both Qualitative And Quantitative Data Were Collected And Adequate Information About Sheep And Goat Fattening And Marketing System By Using Structured And Semi-Structured Questionnaire, Interview, And Through Direct Observation Was Collected And Finally The Data Was Analyzed By Using Statistical Package For Social Science (Spss Version. 22) Software And Microsoft Excel Program Prior To Analysis And Then By Using Descriptive Statistics Such As Table, Number, Graph, Figure, And Others.The Sheep And Goat Fattening Practice In The Study Area Assessed The General Husbandry Issues Such As, Major Feed Resources, Management Practice, Major Constraints And Marketing System. In The Study Area The Most Fattening System Were Traditional Especially In The Chingo Kebele This Was Due To Most Of Households Are Illiterate And They Have No Awareness For Modern Fattening System In This Kebele. The Finishing Of Shoat Was Described As Within The Range Of 3-6 Months With The Percentage Of Three Months 40%, Four Months 33.33%, Five Months 22.22%, And Six Months 4.44%. The Marketing Systems In The Study Area Were From Producer-Consumers And Producer-Local Traders-Consumers.Generally, In The Study Area The Sheep And Goat Fatteners Were Lead Traditional Shoat Fattening Practice And They Use Different Activities To Increase Their Profile By Utilizing Locally Available Feed Resources Especially Khat Residue. The Marketing System Of Sheep And Goat Were Predominantly Characterized As Producer- Consumer And Followed By Producer-Local Trader-Consumer In Some Extent. Farmers Should Enhance Availability Of Feed By Using Different Mechanism. This Can Be Done, As Farmers Should Practice Supplementation Of Available Fed And Production Of Green Feed Even If The Distribution Of The Land Is Too Small. Sheep And Goat Producers Should Have Access To Market Information So As To Adjust Their Marketing Activities.